Metode Efektif Menghafal Al-Qur’an Bagi Siswa Madrasah Ibtidaiyah: - Isna Amalia Akhmar; Hana Lestari; Zulfikar Ismail (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
Al Quran for Muslims is the "Way Of Life" or guidelines for life in this world and the hereafter. So that studying, understanding and memorizing the Al Quran will be more effectively taught from an early age. This study aims to describe the methods used in Madrasah Ibtidaiya educational institutions to print Al-Quran memorizers. The research method is in the form of literature review through a review process by looking for research results through Google Scholar both in the form of journals, scientific papers in the form of theses / theses. The next step is to analyze the data obtained manually and compiled in a narrative. The results showed that there are several well-known methods used in tahfidz institutions, including: Fahmul Mahfudz Method, Tikrarul Mahfudz Method, Kitabul Mahfudz Method, Isati'amul Mahfudz Method. The Talqin Method, the Tasmi 'Method, the Muraja'ah Method. Talaqqi Method, Drill Method, Yanbua Method and so on. At Madrasah Ibtidaiyah, the educational process of memorizing the Koran has different characteristics compared to Islamic boarding schools. This is because in Madrasah Ibtidaiyah the curriculum refers to the National curriculum, so Madrasah Ibtidaiyah must be able to make a tahfidz program that is adapted to other teaching programs. Therefore we need teachers who are able to compile programs by utilizing the available time with an effective and consistent agenda (istiqomah) .Thus, in order for the Tahfidz program at Madrasah Ibtidaiyah to be successful, good planning must be drawn up in terms of Time Management, tahfidz instructors, continue to refine the methods used. applied and strengthened parental support as well as control and motivation.